Spinal Primitive Neuroectodermal Tumor in Children A rare case report and literature review (Journal of Paediatric Surgeons of Bangladesh, 2016)
Primitive neuroectodectodermal tumor is a rare tumor in childhood. It is aggressive childhood malignancies and offer a significant challenge to treatment. An eleven year old female baby presented with fever, pain and neurologic manifestation. Initialy it was diagnose as TB vertebrae and treated accordingly but no improvment rather new metastatic swelling appear after few days. Diagnosis was made by MRI and local tissue biopsy and immunohistohistochemistry. As it is rare and highly invasssive malignancy with poor out come the case was presented along with literature review.J. Paediatr. Surg. Bangladesh 6(2): 64-67, 2015 (July)